2022
DOI: 10.1007/s40171-022-00324-x
|View full text |Cite
|
Sign up to set email alerts
|

Demand and Supply Disruptions During the Covid-19 Crisis on Firm Productivity

Abstract: This paper explores the supply chain (SC) disruption impacts to the performance outcomes of a semiconductor company during the Covid-19 pandemic and proposes appropriate risk mitigation strategies to overcome the crisis. The research uses a single case study methodology and 24 SC employees from Belgium and Germany who take part in the survey. To measure the effect of SC disruptions to the firm’s financial performance, some quarterly financial statement data are used from 2018 to 2021. The regression analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 116 publications
2
14
1
Order By: Relevance
“…On the other hand, NFP evaluates characteristics such as quality, flexibility, delivery duration and innovation, since these contribute to organizational long-term success. Nevertheless, other researchers like Hasan et al (2023), Sayed et al (2022) and Schena et al (2022) agreed that NFP should also be evaluated based on the ability to minimize unplanned disruptions, improve reputations, achieve competitive advantages, customer satisfaction and confidence and the ability to sustain its operational stability. Similarly, Pires and Alves (2022) asserted that nonfinancial indicators are the most appropriate and effective for improving organizational performance in an unpredictable context.…”
Section: Organizational Performancementioning
confidence: 99%
“…On the other hand, NFP evaluates characteristics such as quality, flexibility, delivery duration and innovation, since these contribute to organizational long-term success. Nevertheless, other researchers like Hasan et al (2023), Sayed et al (2022) and Schena et al (2022) agreed that NFP should also be evaluated based on the ability to minimize unplanned disruptions, improve reputations, achieve competitive advantages, customer satisfaction and confidence and the ability to sustain its operational stability. Similarly, Pires and Alves (2022) asserted that nonfinancial indicators are the most appropriate and effective for improving organizational performance in an unpredictable context.…”
Section: Organizational Performancementioning
confidence: 99%
“…The Coronavirus has greatly impacted the semiconductor industry, a key component of technology, due to its globally dispersed supply chain. Semiconductor companies have had to manage rising costs, extended lead times, and supply shortages while meeting customer demand, with most of their production happening overseas (Hasan et al, 2022 )…”
Section: Literaturementioning
confidence: 99%
“…Hasen et al found that 97% of global wealth was affected by supply chain disruptions and that most global disruptions in production capacity and delivery times occurred after one year [2]. Moreover, Accenture's report also shows that high-tech industries such as semiconductor companies are even more severely hampered and that China, a major global semiconductor player, is experiencing a semiconductor crisis [3].…”
Section: Research Backgroundmentioning
confidence: 99%